PREMI TUNGGAL ASURANSI JIWA SEUMUR HIDUP UNIT LINK DENGAN GARANSI MINIMUM DAN NILAI CAP MENGGUNAKAN METODE POINT TO POINT - JULIANTARI, JULIANTARI; SUMARJAYA, I WAYAN; WIDANA, I NYOMAN (E-Jurnal Matematika, 2017)
Unit-linked whole life insurance is an insurance that combines traditional whole life insurance with modern insurance unit-links which provide both protection and investment. One of indexing method for calculating premium of unit-linked insurance is point to point method. The data used in this study was the closing price of PT. Astra Agro Lestari, Indonesia Tbk and The mortality table used in this research is Indonesia’s Mortalita Table III Men. It was obtained that the net single premium for whole life insurance unit-linked for the insured aged 45 years is amounted to Rp. 350.324,-
Keywords: Point to Point method; Unit-Linked; Whole Life Insurance